An overview of Mobile Ad Hoc Networks for the Proactive, Reactive and Hybrid Routing Protocol (International Journal of Engineering and Computer Science, 2017)
A Mobile Ad-Hoc Network (MANET) is an autonomous collection of distributed mobile users. Mobile ad hoc networks (MANETS) can have widely varying characteristics that have a greater impact on the behavior of different routing protocols created for these networks. In this paper, we have compared delay, throughput, routing load and end to end delay of MANET proactive routing protocol (WRP,GSR,DSDV,HSR,CGSR), reactive protocols (AODV, DSR, TORA,ABR,LMR) and hybrid protocol (ZRP,FSR,LANMAR).